Developing Competitive Advantage Strategies for MSMEs: A Case Study of Aroma Khas Poncokusumo Tempe Chips in Malang Regency - Masula, Fariham; Ramadhani, Bima; Putri, Naja Jessyka Maulani; Z, Zulfan Zulkarnaen; Sudarmiatin, Sudarmiatin (International Journal of Business and Applied Economics, 2024)
This research utilizes Porter's Five Forces analysis to assess the development strategies for the competitive advantage of the Aroma Khas Poncokusumo Tempe Chip MSMEs. The primary advantages of these MSMEs are their unique fermentation process, consistent product quality, and high traditional value. Challenges such as the threat of substitute products, supplier dependency, and raw material price fluctuations require innovative approaches. Product diversification, branding enhancement, digital marketing, and customer loyalty programs are identified as effective solutions. These strategies are supported by workforce training and production optimization to ensure business sustainability. This holistic approach enables MSMEs to thrive in a competitive market and contribute to the local economy.